2014
DOI: 10.1177/1940161213519132
|View full text |Cite
|
Sign up to set email alerts
|

May We Have Your Attention Please? Human-Rights NGOs and the Problem of Global Communication

Abstract: Historically, nongovernmental organizations (NGOs) have relied on mainstream news media to expose human-rights violations and encourage governments to pressure the perpetrators. Thanks to the Internet, NGOs are crafting new strategies for conducting information politics. Despite the obvious democratization of access to the means of communication, however, the new media may in fact represent a more challenging environment in which to be heard for some groups seeking global attention. We draw on agenda-setting r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 38 publications
5
65
1
4
Order By: Relevance
“…Within a quantitative survey of social media coverage of 257 human rights organisations, A. Trevor Thrall, Diana Sweet and Dominik Stecula (Thrall et al 2014) discovered that:…”
Section: The Kony 2012 Campaignmentioning
confidence: 99%
“…Within a quantitative survey of social media coverage of 257 human rights organisations, A. Trevor Thrall, Diana Sweet and Dominik Stecula (Thrall et al 2014) discovered that:…”
Section: The Kony 2012 Campaignmentioning
confidence: 99%
“…This competition for attention is a zero-sum game and in this context, the capacity for groups to 'supply' content is likely to differ significantly. Thus groups with low levels of financial resources or without a dedicated or professional press-staff are likely to be able to 'push' less material -and less convincing material -to journalists (Thrall et al, 2014). Thus, purely from a group resource perspective, we would expect media appearances to be highly concentrated.…”
Section: Concentration In Media Appearancesmentioning
confidence: 99%
“…Our current knowledge regarding how and why interest groups get media coverage is scant (see however: Bernhagen & Trani, 2012;Binderkrantz, 2012;Binderkrantz & Christiansen, 2013; de Bruycker and Beyers, 2015;Danielian & Page, 1994;Thrall, 2006;Grossman 2012;Thrall et al, 2014). Most analyses are single country studies, and the few existing comparative studies deal with interest groups as an aggregate category compared to, for example, political parties and bureaucrats (Tiffen et al, 2013;Dimitrova & Strömbäck, 2009).…”
mentioning
confidence: 99%
“…Recent research on human rights NGOs found that while digital media may facilitate new ways in which NGOs access information and promote their work, the "new media may in fact represent a more challenging environment in which to be heard for some groups seeking global attention" (Thrall, Stecula, & Sweet, 2014, p. 135). NGOs that traditionally faced challenges in soliciting resources were further impaired as they faced new "attention bottlenecks" in highly mediatized environments (Thrall et al, 2014). These findings underscore that established communication inequalities and customs can exacerbate prior disparities.…”
Section: Online-offline: Chinese Ngos Are Embedded In Everyday New Anmentioning
confidence: 80%